Sampling Synthesis Technique Applied For The Digital Generation Of Musical Tones Of Malay Folk Instruments - Ang, Yaw Feng (2001)
A random survey of commercial synthesisers available shows that sampled sounds of Malay folk instruments such as the rebab, seruling and others are lacking in both fonns of software or hardware, in sharp contrast to Western classical instrument sounds where similar materials are in abundance. This study attempts to create original sound banks of selected Malay folk instruments in two fonnats, SoundFonts (SFs) and the Downloadable Sounds (DLS) fonnats by application of the sampling synthesis method and analysis of the waveforms of selected instruments. The recorded sound samples of individual selected Malay folk instruments are organised and sequentially edited according to established procedures of trimming, normalisation, conversion and pitch shifting. The identification of the ADSR envelope and frequency components of specific instruments' waveform is also carried out. Finally, the creation of SoundFonts and DLS instruments is undertaken. As a result of this study, the following have been achieved: a) The production of high quality and realistic soft sound banks of selected Malay folk instruments in the SoundFonts (SFs) and the Downloadable Sounds (DLS) formats. b) A detailed analysis of waveforms and frequency components produced by selected Malay folk instruments. It is hoped that these sound banks would be useful as a source of musical tones, applicable for playback of MIDI sequences orchestrated utilising Malay folk instruments, for use by composers as well as commercial products such as synthesisers, samplers and keyboards.